MORPHOLOGY, MOLECULAR IDENTIFICATION, PATHOGENICITY AND FIRST REPORT OF FUSARIUM EQUISETI ASSOCIATED WITH ROOT ROT AND WILT DISEASE OF CATHARANTHUS ROSEUS IN BAGHDAD, IRAQ - Lara B. Yasir; Bushra Subair Abdulsada Almaliky (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted in the Plant Protection Department-College of Agricultural Engineering Sciences - University of Baghdad for the period 2021-2022 with the aim of isolating and identification the pathogens that cause root rot and wilt disease on the Catharanthus roseus plant in different regions of Baghdad by morphological and molecular methods using PCR technique dependence on the ITS region. The results of sampling collection showed the spread of root rot and wilt disease on C. roseus plant in all the regions covered by the study in Baghdad (Al-Gurayat, Al-Sidiyah, Al-Khadhra, Al-Ghazaliya and Al-Dura) and the incidence  rate between 15-85%.The results of isolation and identification showed the presence of 4 types of fungi associated with diseased plant: Fusarium oxysporum, F. solani, F. equiseti and Rhizoctonia solani. All the isolates were differed in their pathogenicity on the dwarf and shrub cultivars of C. roseus, the FeL1 isolate recorded the highest incidence & diseases severity 100 & 65% respectively both cultivars of C. roseus, meaning that there are no significant differences between two cultivars, also the infection intensity of FeL2 isolate was 75% in shrub cultivar, while the control treatment recorded the lowest infection rate and infection intensity reaching 0%. Also, these fungi were diagnosed based on the microscopic and molecular characteristics. The results of the molecular identification showed that the three isolates FeL1, FeL2 and FeL9 belong to the F. equiseti and they showed a conformity ratio of 99.60, 99.39 and 95.97 respectively when compared with the nucleotide sequences of isolates of F. equiseti gene bank of Brazil JQ936262, Ghana OL998428 and China GU586830 respectively. All isolates were recorded in the gene bank and the bank code was given for each isolate. Also, the results confirmed that the sequences belonging to the two isolates (FsL8 and FsL10) gave a conformity ratio of 99.62 and 99.63 respectively when compared with the sequences of KU528858 from Tunis and OM936032 from Pakistan and confirmed their identification as F. solani, while the results of the FoL7 isolation, its identification was confirmed to be related to the F. oxysporum after it showed an conformity ratio of 99.98 with the isolate from China with the number MN96002.